The Value of Ultrasonography in determining Pupillary Light Reflex in Patients with Traumatic Ocular Injuries; a Letter to Editor - Mirjalili, Hamid; Raee Ezzabadi, Ali; Yazdiyousefi, Yeganeh; Jafari Nadoshan, Mohammad Ali (Archives of Academic Emergency Medicine, 2019)
Pupillary light reflex (PLR) measurement is one of the frequent physical examinations used by emergency physicians for assessment of brain stem function and monitoring of intracranial pressure (1, 2). PLR could be abnormal due to various causes such as optic nerve damage, oculomotor nerve damage, brain stem lesion, and using central nervous system depressant drugs, such as barbiturates.